Alpha-2A but not 2B/C noradrenergic receptors in ventral tegmental area regulate phasic dopamine release in nucleus accumbens core. (1st December 2022) - Joanna, Bernacka; Michal, Kielbinski; Agnieszka, Wawrzczak-Bargieła; Katarzyna, Zajda; Marzena, Maćkowiak; Ryszard, Przewlocki; Wojciech, Solecki
Abstract: Adrenergic receptors (AR) in the ventral tegmental area (VTA) modulate local neuronal activity and, as a consequence, dopamine (DA) release in the mesolimbic forebrain. Such modulation has functional significance: intra-VTA blockade of α1 -AR attenuates behavioral responses to salient environmental stimuli in rat models of drug seeking and conditioned fear as well as phasic DA release in the nucleus accumbens (NAc). In contrast, α2 -AR in the VTA has been suggested to act primarily as autoreceptors, limiting local noradrenergic input. The regulation of noradrenaline efflux by α2 -AR could be of clinical interest, as α2 -AR agonists are proposed as promising pharmacological tools in the treatment of PTSD and substance use disorder. Thus, the aim of our study was to determine the subtype-specificity of α2 -ARs in the VTA capable of modulating phasic DA release. We used fast scan cyclic voltammetry (FSCV) in anaesthetized male rats to measure DA release in the NAc after combined electrical stimulation and infusion of selected α2 -AR antagonists into the VTA. Intra-VTA microinfusion of idazoxan – a non-subtype-specific α2 -AR antagonist, as well as BRL-44408 – a selective α2A -AR antagonist, attenuated electrically-evoked DA in the NAc. In contrast, local administration of JP-1302 or imiloxan (α2B - and α2C -AR antagonists, respectively) had no effect. The effect of BRL-44408 on DA release was attenuated by intra-VTA DA D2 antagonist (raclopride) pre-administration. Finally, we confirmed the presence of α2A -AR protein in the VTA using western blotting. In conclusion, these data specify α2A -, but not α2B - or α2C -AR as the receptor subtype controlling NA release in the VTA. Graphical abstract: Image 1 Highlights: Intra-VTA administration of a selective α2A -AR antagonist attenuates phasic DA release. Intra-VTA blockade of α2B - and α2C -AR had no effects on phasic DA release. Effects of α2A -AR antagonist depend on activation of DA D2 receptors in the VTA. α2A -AR protein has been detected in the VTA using Western blotting.